Effect of Different Feeding Programs on Carcass Traits of Broiler Chicks - Shawkat, Sarood Samal; Rashid, Saman Abdulmajid (Sulaimani Journal for Pure and Applied Sciences, 2018)
Four handrad sixty eight day-old broiler chicks of Ross (308) were used during two stages, first a field experiment from 21st September 2015 to 2nd November 2015. Second lab analysis from 10th November 2015 to 8th January 2016. The experiment was applied on two weeks old chicks. The aim of the present research was to identify the effect of skip, remove and dilution of feed on broiler carcass performance. The birds randomly distributed equally into twelve treatments and each treatment subdivided into 3 replicates as follows: T1 = Skip 0 day + Remove nothing + Dilution ratio (0:100) (Control), T2 = Skip 0 day + Remove nothing + Dilution ratio (10:90),T3 = Skip 0 day + Removing time (10:00am – 14:00pm) + Dilution ratio (0:100), T4 = Skip 0 day + Removing time (10:00am – 14:00pm) + Dilution ratio (10:90), T5 = Skip 0 day + Removing time (10:00am – 18:00pm) + Dilution ratio (0:100), T6 = Skip 0 day + Removing time (10:00am – 18:00pm) + Dilution ratio (10:90), T7 = Skip one day + Remove nothing + Dilution ratio (0:100), T8 = Skip one day + Remove nothing + Dilution ratio (10:90), T9 = Skip one day + Removing time (10:00am – 14:00pm) + Dilution ratio (0:100), T10 = Skip one day + Removing time (10:00am – 14:00pm) + Dilution ratio (10:90), T11 = Skip one day + Removing time (10:00am – 18:00pm) + Dilution ratio (0:100) and T12 = Skip one day + Removing time (10:00am – 18:00pm) + Dilution ratio (10:90). Significant improvement (p≤0.05) in the breast percentage for T2 in male and T1 in female when compared with T3 in both sexes, the thigh percentage significant improvement (p≤0.05) for T3 in both sexes when compared with T7. Significant decrease (p≤0.05) in the abdominal fat percentage T3 for male and T4 for female when compared with T11 for male and T9 for female. Significant increased (p≤0.05) in glucose concentration for T4 in both sexes when compared with T6 for male and T5 for female.
Keywords: Broiler; feeding programs; carcass traits